2008
DOI: 10.1080/08927020802256041
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of poly(4-vinyl pyridine) and poly(4-vinyl pyridine)/pyridine composites: structural and optical properties

Abstract: The interactions of the polymer poly(4-vinyl pyridine) moieties with free pyridine molecules in concentrated solution develop protonated and hydrogen-bonded species on the polymer backbone and turn the viscous solution to gel. Direct irradiation at proton transfer centre on the protonated polymer moiety promotes an amorphous-to-crystalline transition. The polymer crystals exhibit completely different optical properties when compared to the amorphous material. The proposed mechanism of the photoinduced crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…DFT modeling of the pyridine and butyl methacrylate side chain moieties were performed with the density functional theory (DFT) code DMol that uses the numerical basis sets, as implemented in Materials Studio 5.5, provided by Accelrys. , A double numerical polarized (DNP) basis set was employed that includes all occupied atomic orbitals, plus a second set of valence atomic orbitals, polarized d -valence orbitals, and a p-orbital on the hydrogen atoms. The Perdew–Burke–Ernzerhof (PBE) gradient corrected functional, that depends on the electron density and its derivative, was applied .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT modeling of the pyridine and butyl methacrylate side chain moieties were performed with the density functional theory (DFT) code DMol that uses the numerical basis sets, as implemented in Materials Studio 5.5, provided by Accelrys. , A double numerical polarized (DNP) basis set was employed that includes all occupied atomic orbitals, plus a second set of valence atomic orbitals, polarized d -valence orbitals, and a p-orbital on the hydrogen atoms. The Perdew–Burke–Ernzerhof (PBE) gradient corrected functional, that depends on the electron density and its derivative, was applied .…”
Section: Methodsmentioning
confidence: 99%
“…Photoconductivity was observed in the gel under irradiation at 385 nm at the proton transfer center N + H, which formed on the polymer side chain . The conductivity was explained as being due to the proton mobility in the excited state and to the conjugated structure of the protonated species. , To expand the spectral range of photosensitivity, we proposed introducing into the P(4VP)/Py gel different types of electron transfer centers in addition to the proton transfer centers. Here, we demonstrate this principle with the example of a polymer gel containing two polymers: poly(4-vinyl pyridine) and poly(4-vinyl pyridine- co -butyl methacrylate) swollen in pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Because of the lone pair of sp 2 electrons, P4VP demonstrates interesting photochemical properties leading to various applications such as coatings that respond to changes in pH. 7 Previously it was suggested that the unique optical properties of the P4VP gel are related to the transfer of a methyne proton to a side chain pyridine nitrogen with the formation of a pyridinium ion NH + . These properties have been studied extensively during the last few years, both experimentally 4-6 and by using computational methods.…”
mentioning
confidence: 99%
“…These properties have been studied extensively during the last few years, both experimentally [4][5][6] and by using computational methods. 7 Previously it was suggested that the unique optical properties of the P4VP gel are related to the transfer of a methyne proton to a side chain pyridine nitrogen with the formation of a pyridinium ion NH + . 8 This suggestion was based on a comparison of the FTIR spectra of the initial P4VP film and the P4VP/pyridine gel in the frequency range of 2800-3200 cm À1 where absorption bands due to the stretching modes of CH and CH 2 groups can be observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation